DYNAMICS OF MSMES IN EAST JAVA FACING THE COVID-19 PANDEMIC - V Ratna Inggawati; Nico Setiawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The COVID-19 pandemic that has hit the world and Indonesia has greatly affected the business world and businesses, including Micro, Small and Medium Enterprises (MSMEs). Various efforts have been made by the government to overcome or at least reduce the impact felt by the community due to this pandemic, from PSBB, PPKM, free vaccination and so on, but this can only be successful if all elements in this country are united and united in overcoming spread of this virus. What about MSMEs? Although this type of business is among the most resilient in the face of all existing situations, without the right innovation and technology, these businesses also receive a negative impact on this pandemic. This article was compiled based on the results of research on 30 MSMEs with research locations in the areas of Surabaya, Gresik, Sidoarjo, Lamongan and Bojonegoro, to find out what the responses and efforts of these MSMEs were to face the pandemic. The selected MSMEs are businesses with evenly distributed criteria among businesses at the micro, small and medium level. Keywords: pandemic-covid 19, MSMEs, government, innovation and technology.